Depois da escola: caminhos trilhados por jovens egressos de uma escola-piloto do novo ensino médio de São Borja - RS - Moura, Thais Costa (2024)
Linked to the Research Line of Educational Public Policies, Educational Practices, and their Interfaces of the Graduate Program in Education at the Federal University of Santa Maria, this research poses the following research problem: How does the New High School contribute to the life projects of young people who attended this stage of education in a pilot school in São Borja (RS)? To address this, the general objective is to understand how the New High School contributes to the life projects of young people who attended this stage of education in a pilot school in São Borja (RS). To achieve this objective, the following specific objectives were defined: (1) To identify who the young people are who completed High School in a pilot school of the New High School in São Borja (RS); (2) To seek the perceptions of the researched young people about the New High School in the pilot school process; and (3) To analyze the paths taken by these young people after completing High School in the pilot school. This is a qualitative research approach, where data were produced from questionnaires consisting of open and closed questions, as well as interviews. Data analysis was carried out based on category analysis by Gomes (2007) and Minayo (2007). The context, as well as the subjects of the research, are young graduates from two pilot schools of the New High School located in the municipality of São Borja (RS). We take as theoretical references authors such as Abramo (1994; 1997; 2005; 2024), Corrochano (2023; 2014; 2024), Dayrell (2005; 2007; 2014), Melucci (2007), Pais (2000; 2003; 2009), Peralva (1997), Weller (2014), Silva (2016; 2018), Silveira (2022; 2024), Reis (2024), and legal documents such as Laws, Decrees, Bills, and Ordinances at the national and state levels that address the High School reform. Through this research, we observe that the researched young people understand High School as a stage of preparation for the job market and/or entry into Higher Education, and therefore, it is necessary to transform this stage of education to bring it closer to the demands of contemporary youth. However, they understand that the recent High School reform, imposed through Provisional Measure No. 746/2016 (later transformed into Law No. 13.415/2017), does not significantly contribute to the development of their life projects, although the need for transformation of High School is one of the arguments taken by reformists in defense of the High School reform.